2016
DOI: 10.1016/j.diii.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of tumor volume reduction in rectal cancer following preoperative chemoradiation

Abstract: MR volumetric measurement of rectal cancer helps predict disease-free survival in patients with rectal cancer who underwent preoperative CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…This evaluation can be performed within days to weeks of the start of the intervention and prior to surgery by assessing volume effects using RECIST criteria with CT or MRI [4,5], MRI based tumour regression grading [6], and mapping macroscopic and microscopic details about tumour architecture [7,8]. Results of prospective trials showed clinical complete response (cCR) or TNM down-staging after CRT is a biomarker of more favourable oncological outcomes in LARC [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This evaluation can be performed within days to weeks of the start of the intervention and prior to surgery by assessing volume effects using RECIST criteria with CT or MRI [4,5], MRI based tumour regression grading [6], and mapping macroscopic and microscopic details about tumour architecture [7,8]. Results of prospective trials showed clinical complete response (cCR) or TNM down-staging after CRT is a biomarker of more favourable oncological outcomes in LARC [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Survival outcomes can be predicted from tumor volume reductions after preoperative CRT [12,16,17]. MRI-based assessments of response to CRT are associated with survival outcomes, including RFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…The TVRR was defined as 100 × [(volume baseline − volume post NAC)/volume baseline]. We classified the patients into two groups according to previously established criteria: good responders (those having a TVRR ≥60) and poor responders (those having a TVRR <60) [12,13]. The sizes of primary lesions and the presence of mrEMVI and ymrEMVI were evaluated by two experienced colorectal surgeons, and incongruent results were reviewed and finalized by consensus.…”
Section: Clinical Tnm Classifications Clinical Crm Mremvi Ymremvimentioning
confidence: 99%
“…The TVRR was defined as 100×[(Volume baseline − Volume post NAC)/Volume baseline]. We classified the patients into two groups according to previously established criteria: good responders (those having a TVRR ≥60) and poor responders (those having a TVRR <60) [12,13]. The sizes of primary lesions and the presence of mrEMVI were evaluated by two experienced colorectal surgeons and incongruent results were reviewed and finalized by consensus.…”
Section: Methodsmentioning
confidence: 99%
“…Survival outcomes can be predicted from tumor volume reductions after preoperative CRT[12, 16, 17]. MRI-based assessments of response to CRT are associated with survival outcomes, including RFS and OS.…”
mentioning
confidence: 99%